Integrating Concrete Manipulatives and Problem-Based Learning to Improve Fraction Addition Outcomes in Elementary Students with Learning Disabilities - Turiang, Marlina; Azizah, Nur (Journal of Innovation and Research in Primary Education, 2025)
Fraction learning poses significant challenges for elementary students, particularly those with learning disabilities who struggle with abstract mathematical concepts. This classroom action research investigated the effectiveness of concrete media-based Problem-Based Learning (PBL) in improving simple fraction addition outcomes for second-grade students with learning disabilities. Conducted over three months at SD Negeri 005 Teluk Pandan, the study employed the Kemmis and McTaggart model across two cycles involving 20 students, including seven with identified learning disabilities. Each cycle comprised planning, action implementation, observation, and reflection phases. Data were collected through achievement tests, structured observations, and document analysis. Results demonstrated substantial improvements: overall class mean scores increased from 62.50 (pre-cycle) to 77.20 (Cycle I) and 83.00 (Cycle II), with 100% of students achieving the learning objective criterion by Cycle II. Students with learning disabilities showed remarkable progress, with mean scores rising from 40.71 to 75.86, representing an 86.3% improvement. All seven students with disabilities reached grade-level competency. The findings suggest that integrating concrete manipulatives with authentic problem-solving contexts creates synergistic effects, addressing multiple learning barriers simultaneously. This integrated approach offers practical implications for inclusive mathematics education, demonstrating that students with disabilities can achieve grade-level competency when provided multisensory, contextually meaningful instruction combining concrete materials with problem-based pedagogical frameworks.